2019
DOI: 10.4081/reumatismo.2019.1140
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-pseudo Meigs’ syndrome: a rare presentation of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory multisystem autoimmune disease. Ascites when associated with pleural effusion and raised CA-125 levels in SLE patient, is known as pseudo-pseudo Meigs’ syndrome (PPMS). This is the case of a 22-year-old lady who presented with complaints of abdominal distension for one month and had a history of spontaneous abortion in the past. Abdominal imaging did not reveal any tumor and after extensive workup a diagnosis of PPMS was made. She was successfully tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Pseudo-pseudo Meigs' syndrome presents with clinical features similar to Meigs' syndrome and pseudo-Meigs' syndrome, including pleural effusion, ascites, and a high CA 125 level, and is easily misdiagnosed. While Meigs' syndrome and pseudo-Meigs' syndrome are secondary to benign ovarian fibromas or other abdominal or pelvic malignancies and resolve after tumour removal, pseudo-pseudo Meigs' syndrome occurs in SLE patients without abdominal or pelvic tumours [9]. The pathophysiology of underlying ascites in pseudo-pseudo Meigs' syndrome is debated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pseudo-pseudo Meigs' syndrome presents with clinical features similar to Meigs' syndrome and pseudo-Meigs' syndrome, including pleural effusion, ascites, and a high CA 125 level, and is easily misdiagnosed. While Meigs' syndrome and pseudo-Meigs' syndrome are secondary to benign ovarian fibromas or other abdominal or pelvic malignancies and resolve after tumour removal, pseudo-pseudo Meigs' syndrome occurs in SLE patients without abdominal or pelvic tumours [9]. The pathophysiology of underlying ascites in pseudo-pseudo Meigs' syndrome is debated.…”
Section: Discussionmentioning
confidence: 99%
“…CA 125 is a commonly used tumour marker, but lacks sensitivity and specificity for ovarian malignancies; its levels can be elevated in other conditions (e.g. SLE) [9]. In inflammatory conditions, CA 125 secretion is increased from the mesovarium and omentum [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLE patients with serositis had greater MUC16 levels and disease duration compared with SLE patients without serositis ( 343 ). Pseudo–pseudo Meigs’ syndrome is a rare manifestation in SLE patients presenting with ascites, pleural effusion, and elevated serum MUC16 levels unrelated to malignancy ( 344 346 ). MUC20 transcript levels were increased with the progression of lupus in the kidneys of MRL/lpr lupus-prone mice ( 347 ).…”
Section: Neus and Mucs In Autoimmune Diseasesmentioning
confidence: 99%
“…This is evident in patients with adenoma, where it was found that the CA125 concentration may reach 100 times its characteristic value [ 102 ]. Among the cases in which CA125 values are increased are lung diseases, including active tuberculosis, with values up to four times, the discriminatory value, which also increases to twice the discriminatory value in pneumonia, chronic obstructive pulmonary disease (COPD), lupus erythematosus, and interstitial lung disease [ 103 , 104 , 105 ].…”
Section: Muc16 (Ca 125) and Non-malignant Proliferationmentioning
confidence: 99%